2009
DOI: 10.1258/td.2008.080382
|View full text |Cite
|
Sign up to set email alerts
|

Death due to chikungunya

Abstract: After its first appearance in Kolkata (Calcutta) during 1963-1965, chikungunya occurred in epidemic form in India in 17 states and union territories. There were 13,90,322 cases suspected to be suffering from chikungunya in 2006, 59,535 in 2007 and 11,222 in 2008; in 2006, 2007 and 2008 there were 15,961, 7,837 and 262 samples, respectively, sent to the National Institute of Virology, Pune, and the National Institute of Communicable Disease, Delhi, for serological diagnosis. Of these, 2001, 1826 and 44, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…In the largest report of children diagnosed with TRALI, the age of reported TRALI cases ranged between 2 and 17 years of age. A potential explanation for the discrepancy in this study is that children in this age group are unique with different underlying pathophysiology; however, this is not supported by previous case reports . It is more likely that children of this age were under recognized by physicians.…”
Section: Discussioncontrasting
confidence: 89%
“…In the largest report of children diagnosed with TRALI, the age of reported TRALI cases ranged between 2 and 17 years of age. A potential explanation for the discrepancy in this study is that children in this age group are unique with different underlying pathophysiology; however, this is not supported by previous case reports . It is more likely that children of this age were under recognized by physicians.…”
Section: Discussioncontrasting
confidence: 89%
“…However, there have been reports of mortality due to Chikungunya fever during the present epidemic in some publications. [44668485] Mavalankar et al . [85] compared the mortality rates in 2006 with those in 2002-2005 for Ahmedabad and found that 2,944 excess deaths occurred during the Chikungunya epidemic (August-November 2006) when compared with the average number of deaths in the same months during the preceding 4 years.…”
Section: Mortalitymentioning
confidence: 99%
“…0.738 deaths/100,000 population (in North Santander department) ( Table 1). As stated by de la Hoz et al [2], previous studies in other continents have reported fatal and severe CHIK [4][5][6][7]. Although fatal cases have not been reported in some important epidemics around the globe, an increased mortality during CHIK outbreaks has been highlighted in countries such as India [8,9] and, in Reunion Island where a CFR of 10.7-27.7% and about 1 death/100,000 population mortality were reported during the 2005-2006 epidemics [10,11].…”
mentioning
confidence: 99%